2015
DOI: 10.1208/s12248-015-9834-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Potency and Degradation Products of Medications Stored Over 550 Earth Days at the International Space Station

Abstract: Abstract. Medications degrade over time, and degradation is hastened by extreme storage conditions. Current procedures ensure that medications aboard the International Space Station (ISS) are restocked before their expiration dates, but resupply may not be possible on future long-duration exploration missions. For this reason, medications stored on the ISS were returned to Earth for analysis. This was an opportunistic, observational pilot-scale investigation to test the hypothesis that ISS-aging does not cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 7 publications
1
50
0
1
Order By: Relevance
“…6 medications changed their physical characteristics compared to 2 on Earth which may affect their efficacy. However, in another study analysis of drug degradation and chemical potency as defined by the API, showed that 8 out of 9 medications met USP criteria for achieving an acceptable API and did not identify unexpected degradation products [103].…”
Section: Use Of Medication In Space -Considerations For Long Term Spamentioning
confidence: 98%
See 2 more Smart Citations
“…6 medications changed their physical characteristics compared to 2 on Earth which may affect their efficacy. However, in another study analysis of drug degradation and chemical potency as defined by the API, showed that 8 out of 9 medications met USP criteria for achieving an acceptable API and did not identify unexpected degradation products [103].…”
Section: Use Of Medication In Space -Considerations For Long Term Spamentioning
confidence: 98%
“…There have been a number of excellent publications either as reviews [1,[82][83][84][85][86][87][88][89] or as original research, including publications which illustrate the effect of gravity on drug targets, processes which affect drug behavior in physiological systems [72,73,86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] and this section will summarise the major findings. When planning astronaut healthcare for a space mission, there are a number of basic considerations which are, in part dependent upon the duration of the mission;…”
Section: Use Of Medication In Space Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…Photolabile drugs were more prone to degradation in space (Du et al 2011). Wotring evaluated stability of nine medicines after 550 days storage in ISS and found that though many pharmaceuticals met USP acceptance criteria for API content, they showed increase in percentage impurities (Wotring 2016). Chuong et al examined stability of vitamin B complex after storage in ISS and observed minute degradation in one of the brands of vitamin B 3 tablets (Chuong et al 2011).…”
Section: Stability Of Pharmaceuticals During Spaceflightmentioning
confidence: 99%
“…It is unlikely to be possible to replace expired drugs on a long journey such as to Mars. Wotring failed to provide a complete guide to this issue because there was no control sample on the Earth and proposed more studies should be carried out [68].…”
Section: Vitamin D Story Continuedmentioning
confidence: 99%